TWEAK and LTβ Signaling during Chronic Liver Disease - Dwyer, Benjamin; Olynyk, John; Ramm, Grant; Tirnitz-Parker, Janina E. (Frontiers in Immunology, 2014)
Chronic liver diseases (CLD) such as hepatitis B and C virus infection, alcoholic liver disease and non-alcoholic steatohepatitis are associated with hepatocellular necrosis, continual inflammation and hepatic fibrosis. The induced microenvironment triggers the activation of liver-resident progenitor cells (LPCs) while hepatocyte replication is inhibited. In the early injury stages LPCs regenerate the liver by proliferation, migration to sites of injury and differentiation into functional biliary epithelial cells or hepatocytes. However when this process becomes dysregulated, wound healing can progress to pathological fibrosis, cirrhosis and eventually hepatocellular carcinoma. The other key mediators in the pathogenesis of progressive CLD are fibrosis-driving, activated hepatic stellate cells (HSCs) that usually proliferate in very close spatial association with LPCs. Recent studies from our group and others have suggested the potential for cytokine and chemokine crosstalk between LPCs and HSCs, which is mainly driven by the tumor necrosis factor (TNF) family members TNF-like weak inducer for apoptosis (TWEAK) and lymphotoxin-β, potentially dictating the pathological outcomes of chronic liver injury.